2017
DOI: 10.1007/s12325-017-0589-5
|View full text |Cite
|
Sign up to set email alerts
|

The Patterns of Non-vitamin K Antagonist Oral Anticoagulants (NOACs) Use in Patients with Atrial Fibrillation in Seven Balkan Countries: a Report from the BALKAN-AF Survey

Abstract: IntroductionData on management of atrial fibrillation (AF) in the Balkan Region are scarce. To capture the patterns in AF management in contemporary clinical practice in the Balkan countries a prospective survey was conducted between December 2014 and February 2015, and we report results pertinent to the use of non-vitamin K antagonist oral anticoagulants (NOACs).MethodsA 14-week prospective, multicenter survey of consecutive AF patients seen by cardiologists or internal medicine specialists was conducted in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…Although our current analysis was subject to loss of almost 50% of the patients due to lack of complete demographic information, the mean ages of patients were ten years younger compared to US studies [20 -22] as well as European studies [21,22]. Prior studies have found that around 30-80% of AF patients are comorbid with several severe conditions such as chronic kidney disease, obesity, coronary arterial disease, diabetes mellitus, hypertension, congestive heart failure, and hyperlipidemia, to name a few [4,15,23].…”
Section: Discussionmentioning
confidence: 78%
“…Although our current analysis was subject to loss of almost 50% of the patients due to lack of complete demographic information, the mean ages of patients were ten years younger compared to US studies [20 -22] as well as European studies [21,22]. Prior studies have found that around 30-80% of AF patients are comorbid with several severe conditions such as chronic kidney disease, obesity, coronary arterial disease, diabetes mellitus, hypertension, congestive heart failure, and hyperlipidemia, to name a few [4,15,23].…”
Section: Discussionmentioning
confidence: 78%
“…The highest proportion of patients treated with apixaban was also declared in The Norwegian Patient Registry [19]. In the present study, a reduced NOAC dose was most often administered to patients treated with dabigatran, just as in the Norwegian Patient Registry [20].…”
Section: Discussionmentioning
confidence: 51%
“…Nonetheless, our survey found that NOACs were only used in approximately 13%, and this was not different whether in elderly or nonelderly subgroups. Of note, other factors such as drug availability on the market or reimbursement policy were shown to guide the use of NOACs for stroke prevention in AF patients in the Balkan Region …”
Section: Discussionmentioning
confidence: 99%